2020
DOI: 10.1177/0021998320980800
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of physical and mechanical properties of aluminium based composites reinforced with titanium diboride particulates

Abstract: Particulate reinforced aluminium matrix composites are one of the most attractive approaches for applications where high strength and hardness combinations are necessary. The aspiration of this study is to investigate the effect of titanium diboride addition on physical and mechanical properties of Al2024-TiB2 composites manufactured using stir casting route, by varying the weight percentages (wt.%) (0, 3, 6 and 9 percent) of titanium diboride particulates. During the casting process, stirring time and speed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Dipankar et al [6] prepared Al2024 + TiB 2 (0, 3, 6 and 9 wt.%) composites using stir casting method where TiB 2 particles are preheated at 450 °C for 30 min. Form results it was concluded that dislocation density improved between matrix and reinforcement as TiB 2 addition refined aluminium alloy grains and improved the microhardness of Al2024-TiB 2 composites.…”
Section: Wettability and Preheatingmentioning
confidence: 99%
See 1 more Smart Citation
“…Dipankar et al [6] prepared Al2024 + TiB 2 (0, 3, 6 and 9 wt.%) composites using stir casting method where TiB 2 particles are preheated at 450 °C for 30 min. Form results it was concluded that dislocation density improved between matrix and reinforcement as TiB 2 addition refined aluminium alloy grains and improved the microhardness of Al2024-TiB 2 composites.…”
Section: Wettability and Preheatingmentioning
confidence: 99%
“…Dipankar et al[6] preheated TiB 2 at 450 °C for 30 min, Ramesh et al[5] preheated TiB 2 at 500 °C and Pazhouhanfar et al[7] preheated TiB 2 at 250 °C for 2 h to get uniform distribution. In all the above-mentioned cases authors have stated that better results were observed with their respective preheating temperatures.…”
mentioning
confidence: 99%
“…The results showed that the percentage elongation reduced with increase in percentage Si3N4 addition in the aluminium matrix. Dipankar Dey et al [10] used stir casting method for fabricating aluminium 2024-TiB2 composites with 0, 3, 6 and 9 weight % of titanium diboride particles. Tensile and hardness tests were conducted.…”
Section: Figure-2: Percentage Elongation Of Compositesmentioning
confidence: 99%
“…In preparing AMCs, "in situ" techniques offer significant advantages over the conventional processing routes and in situ casting route is more economical. In situ type of processing is now in commercial use for TiB 2 particle reinforced aluminum matrix composites [21][22][23]. Moreover, the TiB 2 reinforcement particles in the composite inhibit dislocations, resulting in higher tensile strength.…”
Section: In Situ Castingmentioning
confidence: 99%
“…is interface allows for an efficient load transfer between the matrix alloy and the reinforcement. As the TiB 2 particle content increases, this composite has higher mechanical properties than pure aluminum alloy [22]. Figure 12 displays the experimental arrangement of in situ casting.…”
Section: In Situ Castingmentioning
confidence: 99%